The effects of intense exercise on the female reproductive system - Warren, M. P.; Perlroth, M. E. (Journal of Endocrinology, 2001)
Women have become increasingly physically active in recent decades. While exercise provides substantial health benefits, intensive exercise is also associated with a unique set of risks for the female athlete. Hypothalamic dysfunction associated with strenuous exercise, and the resulting disturbance of GnRH pulsatility, can result in delayed menarche and disruption of menstrual cyclicity. Specific mechanisms triggering reproductive dysfunction may vary across athletic disciplines. An energy drain incurred by women whose energy expenditure exceeds dietary energy intake appears to be the primary factor effecting GnRH suppression in athletes engaged in sports emphasizing leanness; nutritional restriction may be an important causal factor in the hypoestrogenism observed in these athletes. A distinct hormonal profile characterized by hyperandrogenism rather than hypoestrogenism is associated with athletes engaged in sports emphasizing strength over leanness. Complications associated with suppression of GnRH include infertility and compromised bone density. Failure to attain peak bone mass and bone loss predispose hypoestrogenic athletes to osteopenia and osteoporosis. Metabolic aberrations associated with nutritional insult may be the primary factors effecting low bone density in hypoestrogenic athletes, thus diagnosis should include careful screening for abnormal eating behavior. Increasing caloric intake to offset high energy demand may be sufficient to reverse menstrual dysfunction and stimulate bone accretion. Treatment with exogenous estrogen may help to curb further bone loss in the hypoestrogenic amenorrheic athlete, but may not be sufficient to stimulate bone growth. Treatment aimed at correcting metabolic abnormalities may in fact prove more effective than that aimed at correcting estrogen deficiencies.